Achievements of Mesoporous Carbon Solution and Single-Walled Carbon Nanotube Composite on the Sensitive Electrochemical Assay of Ivabradine - Merve Yence; Leyla Karadurmus; Goksu Ozcelikay; Nurgul K. Bakirhan; Sibel A. Ozkan (Analytica, 2021)
In this study, the electrochemical determination of Ivabradine hydrochloride (IH) was studied in detail using a glassy carbon electrode (GCE) modified with mesoporous carbon solution (MCS) and carboxylated group linked single-walled carbon nanotube (SWCNT-COOH). The developed nanosensor showed a significant effect by remarkably increasing the IH signal compared with the bare GCE. Cyclic (CV) and differential pulse voltammetric (DPV) methods were applied to perform electrochemical analysis of IH in pH 3.0 BRB solutions. The calibration plot for IH with a detection limit of 1.47 × 10−7 M was obtained using the DPV technique in the range of 1–10 µM under optimum experimental conditions. The proposed method has been validated and applied for the detection of the IH tablet. The produced nanosensor was also performed for the determination of IH in serum and urine. Excellent recoveries of 98.4%, 98.0%, and 100.2% were achieved for tablet, serum, and urine analysis, respectively.